A rapid prototyped atmospheric non-thermal plasma-activated aerosol device and anti-bacterial characterisation - de Oliveira Mallia, Jefferson; Griffin, Sholeem; Buttigieg, Clara; Gatt, Ruben (Frontiers in Chemistry, 2024)
Non-plasma technologies are being extensively investigated for their potential in mitigatingto mitigate microbial growth through the production of various reactive species. Predominantly, studies utilize utilise atmospheric non-thermal plasma to produce plasma-activated liquids. The advancement of plasma-liquid applications has now led to investigating the investigation of plasma-activated aerosols (PAAs). This study aimed to produce a rapid prototypedrapid-prototyped plasma-activated aerosol setup and perform chemical and anti-bacterial characterization characterisation on the resultant activated aerosols. The setup was produced using stereolithography 3D printing, and air was used as the carrier gas. The novel design of the device allowed for the direct production of PAAs without the prior generation of plasma-activated water and subsequent aerosolisation. The generated aerosols PAAs were assessed for nitrite, hydrogen peroxide and ozone content using colourimetric assays. Antibacterial efficacy was tested against three human pathogenic strains: of Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Salmonella enterica. It was observed that nitrite and ozone contact concentration increased with exposure time, yet no hydrogen peroxide was detected. The generated PAAs showed significant zones of no growth for all bacterial strains. These devices therefore, therefore, show potential to be used as anti-bacterial disinfection technologies.